General neurology: Current challenges and future implications - Bassetti, Claudio Lino Alberto; Accorroni, Alice; Arnesen, Astri; Basri, Hamidon; Berger, Thomas; Berlit, Peter; Boon, Paul; Charway‐Felli, Augustina; Kruja, Jera; Lewis, Steven; Markowski, Michael; Medina, Marco Tulio; et al. (John Wiley and Sons, 2024)
Background and purpose: In the coming decades, the world will face an increasing burden of neurological disorders (ND) and an urgent need to promote brain health. These challenges contrast with an insufficient neurological workforce in most countries, as well as decreasing numbers of general neurologists and neurologists attracted to work in general neurology (GN). This white paper aims to review the current situation of GN and reflect on its future. Methods: The European Academy of Neurology (EAN) task force (TF) met nine times between November 2021 and June 2023. During the 2023 EAN annual meeting, attendees were asked to answer five questions concerning the future of GN. The document was sent for suggestions and eventually approval to the board and the presidents of the 47 national societies of the EAN. Results: The TF first identified four relevant current and future challenges related to GN: (i) definition, (ii) practice, (iii) education, and (iv) research. The TF then identified seven initiatives to further develop GN at both the academic and community level. Finally, the TF formulated 16 recommendations to promote GN in the future. Conclusions: GN will remain essential in the coming decades to provide rapid, accessible, and comprehensive management of patients with ND that is affordable and cost-effective. There is also a need for research, education, and other initiatives aiming to facilitate improved working conditions, recognition, and prestige for those pursuing a career in GN. © 2024 The Authors. European Journal of Neurology published by John Wiley & Sons Ltd on behalf of European Academy of Neurology.